Brincadeiras perigosas e traços de personalidade na adolescência: um estudo de avaliação multimétodo - Machado, Rute da Conceição (2023)
Aggression games (AG), choking games (CG) and challenge games are part of the social phenomenon dangerous games. They are risky behaviors performed in a recreational and peer socialization context. The Dangerous Games have been disseminated among children and adolescents. Furthermore, they have considerable psychosocial implications. In this context, it is essential to develop research that investigates the risk factors associated with these behaviors. The aim of this research was to investigate the relationship between personality traits, emotional characteristics and participation in dangerous games in adolescence. Three studies were developed. In study I, a systematic review of empirical studies was carried out on the prevalence of the practice and/or factors associated with participation in dangerous games. Twenty-seven case reports and 16 cross-sectional studies were analyzed. It was found that the three forms of dangerous play were associated with other risk behaviors and psychopathologies. Regarding study II, 239 adolescents from Fortaleza-CE participated, aged between 12 and 17 years (M = 14.64; SD = 1.69). Five measurement instruments were administered, namely, (1) Sociodemographic Questionnaire, (2) Dangerous Games Questionnaire, (3) Barratt Impulsiveness Scale, (4) Big Five Inventory, and (5) Children's Depression Inventory. Data collection was performed in asynchronous remote format through an online form. Statistical analyzes were performed using the IBM SPSS Statistics 23.0 software. One-way analyzes of variance were performed to assess whether there were differences between the groups with and without a history of practicing JA and/or JNO in relation to depressive symptoms, impulsivity and the big five factors of personality. Significant differences were found between the group of practitioners and non-practitioners of dangerous games with regard to psychological functioning, with different patterns being observed in relation to traits neuroticism [F(3, 239) = 11.95, p < 0.001] and conscientiousness [F(3, 57.66) = 3.76, p = 0.016] and impulsive [F(3, 239) = 7.41, p < 0.001] and depressive [F(3, 50.67) = 7, 19, p < 0.001]. Study II was carried out with 35 adolescents with a history of participation in JA and/or JNO and 35 adolescents with no history of practicing any type of dangerous play. The Pfister Computerized Application System – Pfister Online was administered in a synchronous remote format. The Kruskal-Wallis test was used to verify whether there were statistical differences between the groups with regard to emotional dynamics, assessed using Pfister Online. As a result, there was an increase in shade 2 of red (p = 0.003; r = 0.49) and stimulus syndrome (p = 0.030; r = 0.40) on Pfister Online in the group with a history of participation in AG, compared to the group with no history. In addition, there was an increase in symmetrical formations among students with a history of practicing CG, when compared to those who had never experienced dangerous games (p = 0.007; r = 0.48). The relevance of this work to the scientific literature is highlighted, as empirical data on the specificities of AG and CG in the Brazilian sociocultural context were presented.